2022
DOI: 10.3389/fimmu.2022.973649
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of necroptosis-associated signatures for prognostic and immune microenvironment evaluation in hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma remains the third most common cause of cancer-related deaths worldwide. Although great achievements have been made in resection, chemical therapies and immunotherapies, the pathogenesis and mechanism of HCC initiation and progression still need further exploration. Necroptosis genes have been reported to play an important role in HCC malignant activities, thus it is of great importance to comprehensively explore necroptosis-associated genes in HCC.MethodsWe chose the LIHC coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…There were already necroptosis-related models developed in other cancers. For instance, in hepatocellular carcinoma, consistent with our result, the higher necroptosis risk patients had shorter overall survival and lower efficiency of immunotherapies ( 69 ). In addition, a cell necroptosis index (CNI) was established in triple-negative breast cancer (TNBC) and exactly showed that the poor prognosis of TNBC patients with high-CNI was linked to chemotherapy resistance ( 70 ).…”
Section: Discussionsupporting
confidence: 88%
“…There were already necroptosis-related models developed in other cancers. For instance, in hepatocellular carcinoma, consistent with our result, the higher necroptosis risk patients had shorter overall survival and lower efficiency of immunotherapies ( 69 ). In addition, a cell necroptosis index (CNI) was established in triple-negative breast cancer (TNBC) and exactly showed that the poor prognosis of TNBC patients with high-CNI was linked to chemotherapy resistance ( 70 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we explored the relationship between necroptosis and hepatocellular carcinoma. Although similar studies are available, our study was validated with immunohistochemical experiments in 10 pairs of hepatocellular carcinoma and paraneoplastic samples [ 29 ].…”
Section: Discussionmentioning
confidence: 89%
“…Disrupting pyruvate uptake, which affected TCA cycle, might impair hepatocellular tumorigenesis (Tompkins et al, 2019). In recent years, studies have been reported the relationship between programmed cell death-related phenotypes and HCC, and established corresponding prognostic models (Li and Zeng, 2022;Lu et al, 2022). However, the relationship between a newly found programmed cell death form cuproptosis and HCC was unclear.…”
Section: Discussionmentioning
confidence: 99%